Prevalence, disability, and economic impact of migraine in Spain: a nationwide population-based study - Margarita Sanchez-del-Rio; David García-Azorín; Carmen Peral; Beatriz Armada; Pablo Irimia-Sieira; Jesus Porta-Etessam (The Journal of Headache and Pain)
Abstract Background This study updates data on migraine prevalence in Spain, examining regional variations, healthcare resource utilization (HCRU), and patient-reported outcomes (PROs). Methods Cross sectional study using data from the 2022 National Health and Wellness Survey, an online survey of Spanish residents aged 18 or older. Respondents diagnosed with migraine by a physician and who reported at least one migraine in the past year were considered active migraine cases. Results The study included 7,002 respondents, 930 of whom had physician-diagnosed active migraine. The estimated one-year prevalence of migraine in Spain was 13.1% (95% confidence interval [CI] 12.8–13.4%), with higher rates in females (17.7%, 95% CI 17.2–18.3%) than in males (8.2%, 95% CI 7.8–8.6%). Migraine prevalence varied across Spain’s regions, ranging from 8.1% (95% CI 5.2–11.0%) in Navarre to 19.1% in Cantabria (95% CI 15.6–22.6%). Prevalence was the highest among individuals earning below the median income (14.7%, 95% CI 14.1–15.4%). In the preceding month, 75.3% of patients experienced < 4 migraine days, 15.3% 4–9 migraine days, 4.1% 10–14 migraine days, and 5.3% ≥15 migraine days. Severe disability from migraine was reported by 20.4% of respondents. One in ten people reported using a preventive treatment for migraine. The mean SF-12 scores for mental and physical health were 37.8 and 42.1, respectively, both below the general population norm of 50. The mean EQ-5D summary score was 0.8, indicating reduced quality of life and the PHQ-9 detected severe depressive symptoms in 8.8% of individuals. Work productivity was affected by migraine, with a mean work productivity loss of 35.8%. HCRU in the preceding 6 months was high, with 68.4% having visited at least once a general practitioner, 14.2% a neurologist, 45.6% the emergency room, and 11.8% being hospitalized. The annual cost per person with migraine was estimated at €6,704, primarily driven by indirect costs related to productivity loss. Conclusions Migraine prevalence remains high in Spain, causing a substantial burden and representing a major public health problem. Despite the availability of effective treatments, their usage is limited. Improving migraine management should be prioritized to enhance health outcomes and reduce societal burden. Graphical abstract